Proposed IMC Strategy of BMW Motorrad Indonesia Sport-Line-Up to Increase Brand Awareness in Premium Superbike Segment - Geralldien Zidane; Gallang Perdhana Dalimunthe (Journal of Economics and Business UBS, 2026)
The premium motorcycle industry in Indonesia is shifting from a functional market to a high-involvement lifestyle sector. In this competitive landscape, BMW Motorrad Indonesia dominates with its Adventure (GS) series, but this success has created an internal strategic imbalance where the adventure image heavily overshadows the sport segment. Consequently, the flagship sport lineup (S1000RR and M1000RR) suffers from low top-of-mind awareness and internal cannibalization, despite possessing superior product technology and global brand heritage. This study adopts a qualitative-descriptive approach to formulate a new Integrated Marketing Communication (IMC) strategy. Data were collected through semi-structured interviews with key internal stakeholders (General Manager, Sales, and Marketing) and in-depth interviews with ten external respondents from the target market. The data were analyzed using strategic frameworks including VRIO, Porter’s Five Forces, and SWOT for internal diagnostics, while external consumer insights were processed using NVIVO thematic analysis to identify behavioral drivers. Based on the analysis, this study designs an "Active Digital & Physical Visibility" strategy to disrupt market perception and prioritize brand awareness. The proposed strategy integrates four key components: Visual Decoupling to separate the sport identity from the adventure series; an Influencer Partnership Program to penetrate social algorithms with lifestyle content; Mobile M-Gallery showcases for organic street awareness; and Open Riding Invasions to utilize social proof. This structured IMC plan serves as a roadmap to increase the brand awareness of the sport bike lineup.